2011
DOI: 10.1089/sur.2010.043
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockade Prevents Hematopoietic Progenitor Cell Suppression after Hemorrhagic Shock

Abstract: Background: Severe injury is accompanied by sympathetic stimulation that induces bone marrow (BM) dysfunction by both suppression of hematopoietic progenitor cell (HPC) growth and loss of cells via HPC mobilization to the peripheral circulation and sites of injury. Previous work demonstrated that beta-blockade (BB) given prior to tissue injury both reduces HPC mobilization and restores HPC colony growth within the BM. This study examined the effect and timing of BB on BM function in a hemorrhagic shock (HS) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…This phenomenon of stress induced HPC mobilization is best illustrated by Katayama et al (20) who showed a critical link between the sympathetic nervous system, particularly norepinephrine, and G-CSF induced mobilization. Previously we have shown that norepinephrine causes a dose-dependent reduction of BM HPC growth along with increased HPC mobilization from the BM (12)(13)(14). Therefore, severe trauma along with a prolonged hypercatecholamine state may be deleterious resulting in inhibition of BM HPC growth and continued loss of HPCs into peripheral blood that leads to persistent anemia and abnormal tissue healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon of stress induced HPC mobilization is best illustrated by Katayama et al (20) who showed a critical link between the sympathetic nervous system, particularly norepinephrine, and G-CSF induced mobilization. Previously we have shown that norepinephrine causes a dose-dependent reduction of BM HPC growth along with increased HPC mobilization from the BM (12)(13)(14). Therefore, severe trauma along with a prolonged hypercatecholamine state may be deleterious resulting in inhibition of BM HPC growth and continued loss of HPCs into peripheral blood that leads to persistent anemia and abnormal tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by Katayama et al (20) who demonstrated that the use of a beta-2 agonist augmented G-CSF induced mobilization and propranolol use diminished the mobilization of HPCs in normal mice. BB protects the BM from erythroid growth suppression and diminish HPC mobilization without delaying healing of injured tissue (13,14). High dose propranolol (25 mg/kg) was shown to block the deleterious effects of circulating catecholamines and improve cutaneous wound healing in burned chronically stressed mice (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This hypercatecholamine state after trauma and HS is associated with increased hematopoietic progenitor cell (HPC) mobilization from the bone marrow (BM) and suppression of BM HPC growth, thus contributing to the anemic state. 3,4 After injury and HS, nonselective β-blockade (BB) with propranolol has been shown to not only decrease the mobilization of the HPCs and restore BM HPC growth but also lessen the severity of anemia. 4 …”
mentioning
confidence: 99%
“…1517 In addition, we have previously shown that the use of BB can reduce BM dysfunction associated with injury and HS. 3,4 However, the impact of the sympathetic system and the role of BB on shock-induced distant organ injury is not known. Therefore, the aim of this study was to determine if BB use has systemic protective effects and can diminish gut and lung injury after trauma and HS.…”
mentioning
confidence: 99%